Superior room temperature ductility of magnesium dilute binary alloy via grain boundary sliding. (June 2018) - Somekawa, Hidetoshi; Singh, Alok
Abstract: Fine-grained Mg-Xat.%Bi dilute binary alloys having different concentrations of bismuth element were produced by conventional extrusion process. The ductility decreased with increasing bismuth addition; however, the Mg-0.3 at.%Bi alloy containing binary phase particles exhibited an elongation-to-failure in tension of 170% even at a strain rate of 1 × 10 −3 /s at room-temperature. This superior mechanical property results from grain boundary sliding, which is closely related to equilibrium grain boundary structures. This ductility has never been observed in any other magnesium alloys and the temperature of 0.32 T m for obtaining the present superplastic-like behavior is the lowest among the conventional metallic materials. Graphical abstract: Unlabelled Image